Pengaruh Corporate Governance terhadap Kualitas Sustainability Report - Sherlita, Erly; Brata, Ignatius Oki Dewa; Sujai, R. Achmad Drajat Aji (JURNAL ILMIAH EDUNOMIKA, 2024)
This research concerns about the influence of corporate governance on the quality of sustainability reports. In this study, the samples consist of companies included in Kompas 100 over the 2020–2022 timeframe. Based on the research findings, it can be concluded that the quality of Sustainability Reports is negatively impacted by Non-Executive Directors and the Corporate Responsibility Committee, but not negatively impacted by Independent Non-Executive Directors.